Cytoarchitecture of the Hippocampal Formation in the African Giant Rat (Cricetomys gambianus, Waterhouse) (Nigerian Journal of Physiological Sciences, 2019)
Summary: The African Giant Rat, AGR is an indigenous nocturnal rodent noted for its unique olfactory and cognitive abilities. They have been deployed more recently in the detection of landmines and diagnosis of tuberculosis – two scourges that have had a tremendous negative impact on the African landscape. This olfactory-aided cognition has been linked to the hippocampus. While the anatomical infrastructure of the olfactory bulb of the AGR has been elucidated, little is known about the adaptive cytoarchitecture of the AGR hippocampal formation. This study describes the histological features, including subfields and stratifications of the AGR hippocampus using Nissl and Golgi stains. The basic cytoarchitecture of the AGR hippocampus observed in this study, with respect to stratification, subfields and cell types, is similar to those reported in the laboratory rats. Cell types identified in the AGR hippocampus include pyramidal cells, granule cells and mossy cells with mossy fibers and Schaffer collaterals also delineated. Hippocampal proper subfields CA1 to CA4 were identified. CA3 pyramidal neurons formed a well-defined cell layer starting in between the upper and lower ends of the dentate gyrus and had larger, more distinct pyramidal cells and higher cell layer thickness (240.0±6.0 μm) relative to subfields CA1 (87.0±2.0 μm) and CA2 (109.0±4.20 μm) with significant statistical differences at p